O que faz um Conselho em nível federal?: análise da produção decisória do Conselho Nacional de Assistência Social (CNAS) - 2003-2018 - Bonifácio, Marucelle de Alcântara (2020)
This dissertation aims to analyze the decision-making production of the National Council of Social Assistance (CNAS), exploring the decisions produced over the period of 2003-2018. It was also proposed to discuss the construction of the social assistance sector and how CNAS inserts yourself in this construction, to classify decisions by types of decisions, to identify decision patterns and to draw explanatory hypotheses considering endogenous and exogenous factors to the council. This issue is part of the debate of participatory institutions (PIs) and is part of the study agenda that deals with the effectiveness of PIs. The agenda has advanced to answer questions of co-variations between IPs and outcomes (outcomes) on public policies. In order to contribute to the debate, we opted for a different strategy, to analyze decisions (outputs) as a research limit and as a necessary condition for the occurrence of effects (outcomes). We used the exploratory and descriptive methodology, with a quantitative and qualitative approach, and a case study. For the analysis, we consider the decisions produced by CNAS that are expressed in the form of homologated resolutions, collected through the public and official platform of the council, and classified by the typology based on the publicpolicy cycle model, in the version adapted by Gurza Lavalle, Guicheney, Vello and Rodrigues (2018). We note that in the period 2003-2018, CNAS published 550 normative resolutions. The results revealed that the majority (38.7%) gathers the decisions that self-regulate the board, which deal with management, definition of rules and internal themes to CNAS itself, followed by decisions that affect the moments of planning and definition of general criteria in the social assistance policy, with 36.2%; these two predominant types of decisions make up the board's decision-making pattern. We observed that when acquiring institutional maturity, with more age in its life cycle, CNAS has more active moments focused on the definition of general policy criteria. Throughout the 16 years of analytical analysis, CNAS maintained regularity of decisions and the years 2006 (59 resolutions) and 2007 (48 resolutions) were the moments when the council appears most, with high production of decisions. Almost ten Years after the peak of production, there was a marked variation in the number of decisions taken (14 resolutions in 2015), as well as the year 2017, with 22 resolutions. The work inquired about the incidence of CNAS in public social assistance policy and the case highlights that even though the council spends more of its energies on self-regulation and self-management decisions, the proximity in percentage terms to the policy definition decisions shows that this does not it prevented substantive public policy issues from being discussed and decided, which shows that the CNAS played a fundamental role in structuring the social assistance system and public policy.